Selfish, scared and stupid : the truth about human nature and how to make it work at work - Gregory, Dan; Flanagan, Kieran, 1944- (John Wiley and Sons Australia, Ltd, 2015)
This book is for readers interested in improving influence, growing business reach, improving sales figures or understanding the complexities of human behavior. It answers questions about why the public sometimes fails to engage despite data suggesting otherwise, why new products end up on clearance shelves and why great salespeople often fall short of monthly targets. The book will help readers: learn how the survival of the species plays into business, including delusionary realities and the reasons ideas can fail; discover how to offer customers strategic rewards, thereby making the buying process more attractive to selfish natures; examine the link between fear and the unknown, including strategies for quelling fears and turning them into action; and learn to use a simple mindset to create low-involvement products, helping appeal to instinct and making products hard to resist. The book is built on the idea that businesses must return to a more human engagement methodology in order to succeed. --